Figures-of-Merit of Lateral GaN Power Devices: Modeling and Comparison of HEMTs and PSJs - Luca Nela (IEEE, 2021)
In this work, we propose a simple and yet accurate physical model to describe the figures-of-merit (FOMs) of lateral GaN power devices. While the performance limit of vertical devices is well understood, the FOMs of lateral devices are not properly described by current models. This work investigates the specific characteristics of the depletion in lateral devices, particularly focusing on the substantial potential of Polarization Super Junctions (PSJs) compared to conventional High-Electron-Mobility Transistors (HEMTs). Our results show that PSJs can result in more than a 10-fold decrease in specific on-resistance for the same breakdown voltage compared to HEMTs, which can be further improved by the use of multi-channel heterostructures. In addition, we demonstrate that PSJs lead to a significant reduction of the $R_{ON}× E_{ oss}$ figure-of-merit, both in the case of negligible and dominating parasitic contributions. This model enables a proper evaluation of the main figures-of-merit of lateral GaN power devices and shows the potential of PSJs to reduce both the DC and switching losses in power devices.